THE ROLE OF USING REAL OBJECT MEDIA IN EXPLAINING ELECTRICAL CIRCUITS TO PHYSICS STUDENTS OF JABAL GHAFUR UNIVERSITY - Hamdi Hamdi; Muhammad Saiful (International Journal of Social Science, 2023)
One of the media that can be used in learning physics in the Physics Study Program is the tools available in the laboratory. This research was carried out at the Physics Study Program at Jabal Ghafur University entitled ““The Role of Using Real Material Media in Explaining Electrical Circuits to Physics Students at Jabal Ghafur University. The use of media in the physics learning process is a demand in the curriculum. Media in the learning process can be used in the form of original objects or in the form of pictures. Formulation of the problem: "Is there a role for the use of real-life media in explaining electrical circuits to Physics Students in Even Semester Academic Year 2022/2023?" : "There is a role for the use of real-life media on student achievement in electrical circuits in the Physics Study Program." The population in this study were all Physics Study Program students. While the samples in this study were taken by random sampling (drawn or random) each 30 people, the number of both classes = 60 people. The method for collecting data is the "experimentation method". The research instrument is: is the "Test", Data processing method: use "Z-score". Conclusion, "There is a role for the use of real-life media on student learning achievement in electrical circuit material for the 2022/2023 Academic Year Semester"